Electrophoretic co-deposition of chitosan and graphene oxide results in antibacterial coatings for medical applications - Metze,AL; Pishbin,F; Ryan,MP; Seuss,S; Diba,M; Shaffer,MSP; Boccaccini,AR (2015)
Chitosan - graphene oxide (GO) composite coatings intended for antibacterial applications were obtained by cathodic electrophoretic deposition (EPD) on stainless steel. The coatings were characterized using SEM, FTIR, contact angle and roughness measurements and by antibacterial studies against E.coli. The coating was observed to consist of a polymer matrix with embedded, agglomerated graphene oxide sheets. A decrease in bacteria cell viability of at least 50 % was measured on the chitosan - GO surface in comparison to uncoated stainless steel.